2022
DOI: 10.3389/fchem.2022.1035691
|View full text |Cite
|
Sign up to set email alerts
|

Recent progresses and challenges in aqueous lithium–air batteries relating to the solid electrolyte separator: A mini-review

Abstract: The lithium–air (Li–air) battery utilizes infinite oxygen in the air to store or release energy through a semi-open cathode structure and bears an ultra-high theoretical energy density of more than 1,000 Wh/kg. Therefore, it has been denoted as the candidate for next-generation energy storage in versatile fields such as electric vehicles, telecommunications, and special power supply. Among all types of Li–air batteries, an aqueous Li–air battery bears the advantages of a high theoretical energy density of more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…[36] To address this issue, a polymer, inorganic, or liquid buffer layer should be deposited or coated between the electrolyte and lithium anode, which is characterized by high Li-ion conductivity, flexibility, and endurance with the lithium electrode. [37][38][39] By sputtering Li 3 PO 4 under a nitrogen discharge, a lithium phosphorous oxynitride (LiPON) thin film layer was obtained and applied in the early stage. [40] PEO with different Li salts, as Zhang et al suggested, was also deployed as a polymer interlayer material which has successfully suppressed the undesirable reaction between the LATP and Li metal anode.…”
Section: Solid-state Lithium-air Batteriesmentioning
confidence: 99%
“…[36] To address this issue, a polymer, inorganic, or liquid buffer layer should be deposited or coated between the electrolyte and lithium anode, which is characterized by high Li-ion conductivity, flexibility, and endurance with the lithium electrode. [37][38][39] By sputtering Li 3 PO 4 under a nitrogen discharge, a lithium phosphorous oxynitride (LiPON) thin film layer was obtained and applied in the early stage. [40] PEO with different Li salts, as Zhang et al suggested, was also deployed as a polymer interlayer material which has successfully suppressed the undesirable reaction between the LATP and Li metal anode.…”
Section: Solid-state Lithium-air Batteriesmentioning
confidence: 99%
“…The depletion of fossil fuels and environmental degradation have led to the development of renewable energy, such as solar and wind energy, and to meet the intermittent problems of these energy production, the exploration and research of energy storage equipment is essential. Due to the limitation of cost and safety issues of traditional lithium-ion batteries, aqueous metal-air batteries have become the choice of the next-generation (Chen et al, 2022), among which Rechargeable zinc-air battery (ZAB) are most noteworthy (Wu et al, 2022) due to high energy density of 820 mA h/g which is about 5 times higher than the current lithium-ion battery (Li et al, 2013;Liu Q. et al, 2019), operate safely due to the use of non-flammable aqueous electrolyte, rich earthabundance of Zn (Li and Dai, 2014). So it can provide stable discharge voltage for electrical vehicles, grid energy storage, even some advanced electronics, such as a robot (Goldstein et al, 1999;Yang et al, 2011;Li et al, 2013;Lutkenhaus and Flouda, 2020;Zhao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Four main types of LABs can be distinguished: 9 (i) LABs with an aqueous electrolyte, 22,23 (ii) LABs with a nonaqueous electrolyte, 24,25 (iii) hybrid cells (an organic solvent at the anode compartment and an aqueous solvent at the cathode compartment), 26 and (iv) LABs with a solid electrolyte. 10,27 The application of solid electrolytes can improve the properties of LABs. For example, metal-oxide-based materials are stable at elevated temperatures and their electrochemical stability is significantly higher than that of organic solvents, providing high (up to 6 V) operation voltage.…”
mentioning
confidence: 99%
“…9 The lithium anode can react with oxygen and moisture (originating from ambient air); thus, especially for aqueous cells, a special layer is required to prevent these side reactions. 10 Furthermore, special gas diffusion layers (GDLs) are applied at the cathode compartment [11][12][13] to prevent the evaporation of solvents and the diffusion of water from the ambient air into the cell while providing appropriate oxygen transport. In addition to the application of GDLs, protective polymer films 14,15 can be used on the surface of lithium.…”
mentioning
confidence: 99%